Implementation of a new programme for the surgical treatment of CTEPH in the Czech Republic--Pulmonary endarterectomy - Lindner, J; Jansa, P; Kunstyr, J; Mayer, E; Blaha, J; Palecek, T; Aschermann, M; Grus, T; Ambroz, D; Tosovský, J; Vitkova, I (The Thoracic and cardiovascular surgeon, 2006)
BACKGROUND: Chronic thromboembolic pulmonary hypertension (CTEPH) in indicated cases can be successfully cured by endartectomy of pulmonary arteries (PEA). Symptomatic nontreated CTEPH has a very poor prognosis; the five-year survival rate in patients with a medium pressure of over 50 mmHg in the main pulmonary artery is as low as 10 %. This kind of operation was previously not available in the Czech Republic. In 2004, a PEA programme was launched at the Cardiocentre of the General Teaching Hospital in Prague in co-operation with the institution of a well known specialist in this field (Prof. Mayer, Johannes Gutenberg University in Mainz, Germany). PATIENTS: Between September 2004 and January 2006, 21 patients (14 males and 7 females; average age 48 years) with CTEPH were operated on, after a complex investigation. The mean pressure in the main pulmonary artery in these patients was 54.8 mmHg; 7 patients suffered from coagulopathy. METHOD: The new surgical technique, modifications of which are used at most facilities, was developed by Jamieson and Daily at the University of California in San Diego: an arrest of circulation in deep hypothermia to protect the brain is vital for the visualisation of distal branches of the pulmonary artery. RESULTS: 21 patients were operated on with a mortality of 4.76 % (1 patient died). Other surgeries performed were suture of a defect of the atrial septum (three times), aortocoronary bypass (three times), and cryoablation of the right atrium for flutter (once). The average circulatory arrest time was 42 minutes, the average total pumping time was 331 minutes, and the average total duration of an operation was 450 minutes; the average duration of mechanical ventilation was 58 hours. Within one month there was a considerable improvement or normalisation of haemodynamic parameters and an increase in the average walking distance on the six-minute walking test by 132 metres. CONCLUSIONS: PEA is a curative method for patients with CTEPH with a surgically accessible obstruction of the pulmonary artery. Centralisation of the care of these patients is a rational necessity, as this enables the centre to gain a maximum of experience with this complicated diagnosis and treatment. Multidisciplinary co-operation is a sine qua non for success in these programmes.
Keywords: Česká republika; lidé středního věku; Czech Republic; Hypertension, Pulmonary; Male; arteria pulmonalis; lidé; Female; plicní hypertenze; ženské pohlaví; endarterektomie; mužské pohlaví; Middle Aged; Humans; Pulmonary Artery; Endarterectomy